2023
DOI: 10.3390/ijerph20021313
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dry Eye Symptoms and Associated Risk Factors among University Students in Poland

Abstract: Aim: The aim of the study was to demonstrate the prevalence and risk factors of dry eye symptoms (DES) among university students in Poland. Material and methods: A cross-sectional study survey was conducted among 312 Polish university students. The questionnaire consisted of the Ocular Surface Disease Index (OSDI), the 5-Item Dry Eye Questionnaire (DEQ-5) and questions regarding medical history and risk factors. Results: According to the OSDI, more than half of respondents (57.1%) have symptoms of ocular surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 75 publications
1
10
0
Order By: Relevance
“…However, in a study published by Wróbel-Dudzinska et al, in which 312 university students were evaluated for dry eye prevalence and risk-factor preponderance, a total of 219 were women, of which nearly 22% (47 out of 219) declared oral contraceptive use, the authors considered oral contraceptive use a risk for dry eye. 43 …”
Section: Discussionmentioning
confidence: 99%
“…However, in a study published by Wróbel-Dudzinska et al, in which 312 university students were evaluated for dry eye prevalence and risk-factor preponderance, a total of 219 were women, of which nearly 22% (47 out of 219) declared oral contraceptive use, the authors considered oral contraceptive use a risk for dry eye. 43 …”
Section: Discussionmentioning
confidence: 99%
“…Sheppard and Wolffsohn 24 and Yammouni and Evans 25 show that contact lenses and light-filtering spectacles potentially help to mitigate DES symptoms. Other studies, including Markoulli et al 26 and Wróbel-Dudzińska et al 14 found that spectacles-and contact lens-related problems resulting in stress, lower wearing time, conjunctiva staining, more chair time, and ultimate discontinuation heighten the risk of DES. Similarly, taking frequent breaks and using dry eye or tear supplements reduce the odds by 0.3 and 0.55, respectively.…”
Section: Computer Use Characteristicsmentioning
confidence: 96%
“…Internal risk factors are chiefly related to the existence of untreated pre-existing eye problems, such as astigmatism, ametropic or refractive errors such as far or nearsightedness, and poor accommodation. 8,13,14 On the other hand, risk factors for external symptoms of DES mainly flow from poor ergonomic practices, including workstation situation, uncomfortable position, prolonged viewing of digital screens, improper lighting conditions, uncommon blinking, glare, and incorrect distances between the eye and the device. Recent studies showed high prevalence of DES, unsatisfactory knowledge about DES and poor preventive ergonomic practices.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, our study aims to determine the prevalence of DED among the general population and investigate its association with dry skin during the pandemic. The scores for DED symptoms ranged from 0 to 100, classifying them as none (0-12), mild (13)(14)(15)(16)(17)(18)(19)(20)(21)(22), moderate (23)(24)(25)(26)(27)(28)(29)(30)(31)(32), or severe (33). To identify DED, we used a cut off value of ≥22.…”
Section: Studies Bymentioning
confidence: 99%
“…The Baumann skin-type questionnaire assessed the skin type (oily or dry) based on nine questions (Figure 1). Skin types were classified as very dry skin (9-15), slightly dry skin (16)(17)(18)(19)(20)(21)(22), slightly oily skin (23)(24)(25)(26)(27)(28)(29), and very oily skin (30)(31)(32)(33)(34)(35)(36) based on the scores. (Figure 2).…”
Section: Studies Bymentioning
confidence: 99%